2019
DOI: 10.1021/acscatal.8b04251
|View full text |Cite
|
Sign up to set email alerts
|

Structure- and Temperature-Dependence of Pt-Catalyzed Ammonia Oxidation Rates and Selectivities

Abstract: Ammonia oxidation is operated at different temperatures over Pt catalysts of different structures to recover different products. In this work, we elucidate the dependency of ammonia oxidation rates and selectivities on both Pt structure and temperature. We perform density functional theory (DFT) computations to compare the reaction and activation energies of elementary reactions on Pt(211) and Pt(111). We develop a microkinetic model parametrized with the DFT results. We show that barriers to product formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 53 publications
2
73
0
1
Order By: Relevance
“…The difference in S N2 values in the range of ∼275–400 °C is 10 % for Pt/Al 2 O 3 catalysts with platinum particles of ∼1, ∼2.6, and ∼8 nm. Larger Pt particles show higher N 2 selectivity due to a large number of terraces on the surface [25c] . Note that higher S N2 was found at T<200 °C over smaller Pt crystallites [8a] .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The difference in S N2 values in the range of ∼275–400 °C is 10 % for Pt/Al 2 O 3 catalysts with platinum particles of ∼1, ∼2.6, and ∼8 nm. Larger Pt particles show higher N 2 selectivity due to a large number of terraces on the surface [25c] . Note that higher S N2 was found at T<200 °C over smaller Pt crystallites [8a] .…”
Section: Discussionmentioning
confidence: 92%
“…N ad species prevail on the platinum surface, leading to the predominant formation of N 2 at low temperatures. At high temperatures, the amount of NO ad grows [25c,38] increasing the N 2 O yield (Figure S2). Considering the reaction scheme described above, it might be concluded that the low‐temperature peaks in the N 2 /N 2 O concentration curves are associated with the desorption of N ad and NO ad intermediates in the form of products, while the second peak is due to the steady‐state reaction taking place at higher temperature.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that beside the choice of material, the structure and temperature dependence of the catalyst plays an important role on ammonia oxidation rates and selectivity. 154 Materials that show promising activity towards AOR can be categorized into three groups: 159 It has been reported that in many cases, the latter species is responsible for ammonia oxidation and its activity for such is well documented. 160,161 A direct electron transfer mechanism from ammonia to NiOOH has been suggested, as shown in Equation 13.…”
Section: Choice Of Anode and Cathode Electrocatalysts For Ammonia-fedmentioning
confidence: 99%
“… 30 The higher TOF for the Pt overlayer (Pt/SUS) relative to that for Pt nanoparticles (Pt/Al 2 O 3 ) can be explained by the different oxidation behavior of Pt: metallic Pt nanoparticles were easily oxidized during the NH 3 oxidation reaction, whereas the metallic Pt overlayer was more stable in Pt/SUS. NH 3 oxidation on Pt proceeds via N–H bond cleavage activated by dissociatively adsorbed O 2 , 42 44 and metallic Pt is a superior catalyst to Pt oxides for the O 2 dissociation. 15 , 42 However, the details of the mechanism for the high-TOF NH 3 oxidation over the present Ir overlayer catalyst have remained unknown.…”
Section: Results and Discussionmentioning
confidence: 99%